Material Affective Engagements: Examples from Ancient Mesopotamia - Steinert, Ulrike; Colombetti, Giovanna (Aestimatio, 2022)
This article applies approaches from current emotion research on material affective scaffolds—objects made and used to enhance, and more generally transform, affective states—to the emerging field of study focusing on emotions in ancient Near Eastern societies. Its main goal is to extend the framework of 4E cognition—with its central notion that human cognition is embodied, embedded, enactive, and extended—to the realm of affective states, emphasizing that through our bodily interactions with material objects we transform not just our cognitive processes but also our emotions, moods, and so forth. Thereby, the present study seeks to contribute to the exploration of the relationships between sensory experiences, emotions, moods, and the material world by investigating the affective meanings that material things acquire through people’s entanglements with them.The study focuses on one particular class of objects—Mesopotamian amulets from the first millennium BC, which served as bodily adornments but were also understood to have the power to evoke affective responses through their activation in ritual performances. Referring to scholarly compendia in Mesopotamian cuneiform texts, this study demonstrates that these objects were recommended by healing experts to influence different affective states, both in oneself and others. It examines the connection between affective states and specific material features of the amulet components (consisting of minerals, metals, and plant and animal substances). Finally, Mesopotamian views of affective states and their management are compared with those of contemporary cognitive-affective science. This comparison shows that although there are some analogies, there are also important differences that depend mainly on different understandings of the human mind and agency.